2020
DOI: 10.1016/j.thromres.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of asymptomatic deep vein thrombosis in patients with COVID-19 pneumonia and elevated D-dimer levels

Abstract: An increased risk of venous thromboembolism (VTE) in patients with COVID-19 pneumonia admitted to intensive care unit (ICU) has been reported. Whether COVID-19 increases the risk of VTE in non-ICU wards remains unknown. We aimed to evaluate the burden of asymptomatic deep vein thrombosis (DVT) in COVID-19 patients with elevated D-dimer levels. Method: In this prospective study consecutive patients hospitalized in non-intensive care units with diagnosis of COVID-19 pneumonia and D-dimer > 1000 ng/ml were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
385
6
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(440 citation statements)
references
References 21 publications
(25 reference statements)
28
385
6
11
Order By: Relevance
“…The main ndings of the present study were that D-dimer level and Troponin levels were detected higher than normal in COVID-19 positive trauma patients, although no signi cant vascular pathology could be detected in these COVID-19 positive trauma patients, as reported in the literature (19,20).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The main ndings of the present study were that D-dimer level and Troponin levels were detected higher than normal in COVID-19 positive trauma patients, although no signi cant vascular pathology could be detected in these COVID-19 positive trauma patients, as reported in the literature (19,20).…”
Section: Discussionsupporting
confidence: 61%
“…In a multicentre study of 184 patients with severe COVID-19 from the Netherlands, 28 (15.2%) VTE cases were reported and the cumulative incidence of VTE was estimated to be 27% (39). Rodriguez et al stated that 23 of 156 patients had DVT in their retrospective study and as in other series, the probability of developing DVT was high in patients with COVID-19 positivity and a high D-dimer level (19). The low incidence of DVT in the patients in the current series can be considered to be due to the initiation of antithrombotic medication and wearing antiembolic socks from the time of hospitalization, and in-bed exercise was also started immediately on hospitalization.…”
Section: Discussionmentioning
confidence: 93%
“…In our multiple logistic regression model, patients with pulmonary infection experienced an increased risk of DVT. A higher risky relevance of pulmonary infection with DVT was also demonstrated in other researches (14,15). A research on the psychiatric inpatients revealed that the average in-hospital incidence of DVT was up to 10%, while the DVT risk in the group with pulmonary infection was signi cantly increased (16).…”
Section: Analysis Of the Changes In Laboratory Variables When Dvt Detsupporting
confidence: 58%
“…Interestingly, we compared the laboratory variables in different times and found that the level of D-dimer was signi cantly higher when DVT detected than that on admission, which suggested that dynamically testing D-dimer could be a predictive method for DVT. D-dimer as a sensitive marker for thrombus formation ,was an indicator for predicting DVT in different disorders (12,15,26). In the current studies, Ddimer demonstrated a sensitivity of 85%-95% and a speci city of 25%-50% for DVT (27,28).…”
Section: Analysis Of the Changes In Laboratory Variables When Dvt Detsupporting
confidence: 49%
“…[1,[3][4][5][6][8][9][10][11][12][13][14][15] Seven studies routinely screened VTE in every patient using lower-extremity venous ultrasound scanning, and this study group was prede ned as the "routine screening group." [16][17][18][19][20][21][22] Our primary aim was to determine the incidence of VTE in COVID-19 patients in two prede ned cohort subtypes:…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%